2013
DOI: 10.2147/ott.s40992
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor activity of dichloroacetate on C6 glioma cell: in vitro and in vivo evaluation

Abstract: Dichloroacetate (DCA), a small molecule mitochondria-targeting agent, can penetrate the blood–brain barrier, showing potential therapeutic effects on brain tumors. Considering the effects of DCA on tumor cellular metabolism, penetrating across the blood–brain barrier, as well as having potential antitumor activity on brain tumors, the purpose of this study is to investigate the antitumor activity of DCA on C6 glioma cells in vitro and in vivo. DCA inhibited C6 glioma cell proliferation, induced C6 cell apoptos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 48 publications
(51 reference statements)
1
15
0
4
Order By: Relevance
“…In the present study, the IC 50 values of DCA are relatively high (≥20 mM, 72 hr) to halt the proliferation of GBM cells in culture, which is consistent with most of the studies in vitro [ 13 , 23 , 24 , 39 - 43 ]. On the other hand, in vivo studies testing DCA on pre-clinical rodent models with different types of malignancy demonstrated encouraging results with effective doses of 50–200 mg/kg/day [ 39 , 40 , 44 ], which translates into approximately 13 kg/kg/day in human resulting in the serum level of 0.5-1 mM [ 15 , 40 ]. Therefore, the in vivo achievable concentration (0.5-1 mM) may not necessarily be correlated with the supraphamacological level (5–50 mM) tested in vitro for this anti-metabolic compound.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, the IC 50 values of DCA are relatively high (≥20 mM, 72 hr) to halt the proliferation of GBM cells in culture, which is consistent with most of the studies in vitro [ 13 , 23 , 24 , 39 - 43 ]. On the other hand, in vivo studies testing DCA on pre-clinical rodent models with different types of malignancy demonstrated encouraging results with effective doses of 50–200 mg/kg/day [ 39 , 40 , 44 ], which translates into approximately 13 kg/kg/day in human resulting in the serum level of 0.5-1 mM [ 15 , 40 ]. Therefore, the in vivo achievable concentration (0.5-1 mM) may not necessarily be correlated with the supraphamacological level (5–50 mM) tested in vitro for this anti-metabolic compound.…”
Section: Discussionsupporting
confidence: 92%
“…In 2017, a study on flow-induced metabolic reprogramming in ECs reported that HIF-1α increased PDK-1, which reduced mitochondrial respiratory capacity [ 10 ]. On cancer cells from various origins, it has been shown that DCA, a PDK inhibitor currently studied in clinical trials, decreased HIF-1 activity, resulting in a reduced expression of HIF-1α target genes including pro-angiogenic factors [ 11 , 12 ] and a decreased tumor angiogenesis [ 12 , 13 , 14 , 15 , 16 ]. To our knowledge, besides this HIF-1α mediated effect by cancer cells, a direct effect of DCA through a metabolic reprogramming of ECs has not been previously considered.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been recently been tested in phase I clinical trials to treat patients with advanced solid tumors [15] , [16] . DCA exhibits potent anti-cancer activity in cancer cells [17] , [18] and animal models [12] , [19] , [20] , via inducing oxidative stress that causes apoptosis in cancer cells [21] , [22] . Similarly, DCA exhibited protective effects on hypoxia-induced pulmonary hypertension via inducing apoptosis of the pulmonary smooth muscle cells [23] , [24] .…”
Section: Introductionmentioning
confidence: 99%